(untitled) (Scientific journal of the Fergana State University, 2023)
The article is devoted to the study of the chemical components of the aboveground part of the medicinal plant Melilotus officinalis (L.) Pall (sweet clover) and Melilotus albus of the Fabaceae family Three phenolic compounds were isolated from chloroform-ethyl acetate fractions of 75% alcohol extract of the above-ground part of Melilotus officinalis. Based on the study of UV, 1H, 13C NMR, HSQC, and HMBC spectra, the isolated substances were identified with dihydrocoumarin, melilotic acid, and E-melilotoside. The component composition of the essential oil of the air-dry aerial part of Melilotus albus obtained by hydrodistillation was studied by the GC-MS. The main component of the essential oil is coumarin, which content is 97.92%.